Employee health and employer incentives - Hullegie, Patrick; Koning, Pierre (Bonn, 2015)
"In the past two decades the OECD has regularly voiced concern about the labor market exclusion of people with disabilities and about the cost of disability insurance programs. This paper examines whether the fundamental disability insurance reforms that were implemented in the Netherlands have helped or hindered employment opportunities of workers with health problems or disability. An important component of the Dutch reforms was to enhance employer incentives, which was done by making them responsible for paying sickness benefits and by strengthening their sickness monitoring obligations. These employer incentives may stimulate preventive and reintegration activities by firms, thereby improving the employment opportunities of disabled workers. However, the reforms also impose substantial costs on employers when an employee gets sick and may therefore reduce employment opportunities of disabled workers. We use data from the Dutch Labor Force Survey and rich administrative data from hospital admission records, social security records, and the municipality registers containing demographic information to examine whether the disability reforms have in fact improved the economic situation for the disabled. On balance, we conclude that the DI reforms implemented by the Dutch government have mainly protected those who already have a job, and may have inadvertently reduced the hiring opportunities of people with a disability."